Hydrothermal Precipitation of Sanidine (Adularia) Having Full Al, Si Structural Disorder and Specular Hematite at Maunakea Volcano (Hawai'i) and at Gale Crater (Mars). Issue 9 (10th September 2020) - Morris, R. V.; Rampe, E. B.; Vaniman, D. T.; Christoffersen, R.; Yen, A. S.; Morrison, S. M.; Ming, D. W.; Achilles, C. N.; Fraeman, A. A.; Le, L.; Tu, V. M.; Ott, J. P.; et al.
Abstract: Hydrothermal high sanidine and specular hematite are found within ferric‐rich and gray‐colored cemented basaltic breccia occurring within horizontal, weathering‐resistant strata exposed in an erosional gully of the Pu'u Poliahu cinder cone in the summit region of Maunakea volcano (Hawai'i). The cone was extensively altered by hydrothermal, acid‐sulfate fluids at temperatures up to ~400 °C, and, within strata, plagioclase was removed by dissolution from progenitor Hawaiitic basalt, and sanidine and hematite were precipitated. Fe2 O3 T concentration and Fe 3+ /∑Fe redox state are ~12 wt.% and ~0.4 for progenitor basalt and 46–60 wt.% and ~1.0 for cemented breccias, respectively, implying open‐system alteration and oxic precipitation. Hydrothermal high sanidine (adularia) is characterized by full Al, Si structural disorder and monoclinic unit‐cell (Rietveld refinement): a  = 8.563(19) Å, b  = 13.040(6) Å, c  = 7.169(4) Å, β  = 116.02(10)°, and V  = 719.4(19) Å 3 . Hematite (structure confirmed by Rietveld refinement) is the predominant Fe‐bearing phase detected. Coarse size fractions of powdered hematite‐rich breccia (500–1000 μm) are dark and spectrally neutral at visible wavelengths, confirming specular hematite, and SEM images show platy to polyhedral hematite morphologies with longest dimensions >10 μm. Smectite and 10‐Å phyllosilicate, both chemically dominated by Mg as octahedral cation, are additional diagenetic hydrothermal alteration products. By analogy and as a working hypothesis, high sanidine (Kimberly formation) and specular hematite (Mt. Sharp group at Hartmann's Valley and Vera Rubin ridge) at Gale crater are interpreted as diagenetic alteration products of Martian basaltic material by hydrothermal processes. Plain Language Summary: A layer of weathering‐resistant material is located within the walls of an erosional gully of the Pu'u Poliahu cinder cone in the summit region of Maunakea volcano (Hawai'i). The volcanic cone, initially composed of unaltered basaltic material (tephra), was extensively altered throughout by hot, sulfuric‐acid solutions. The layer is a location where the alteration by hot water was particularly aggressive, cementing the volcanic sediment and causing extensive chemical and mineralogical changes. Instead of basaltic chemical and mineralogical compositions, altered tephra was enriched in iron from aqueous precipitation of the mineral hematite (Fe2 O3 ) and was characterized by high sanidine with full structural disorder as the feldspar (instead of plagioclase, which was removed by dissolution) and by Mg‐rich phyllosilicates as additional precipitation products. Hematite, often present as a red pigment in geologic materials, was precipitated from the hot water as specular (i.e., gray) hematite. By analogy, high sanidine and specular hematite at Gale crater (Mars) can be interpreted as alteration products of preexisting Martian basaltic sediment by hot‐water solutions. Key Points: High sanidine (full Al, Si structural disorder) and specular hematite hydrothermally precipitated on basaltic Maunakea volcano, Hawai'i Smectite and 10‐Å phyllosilicate (both Mg‐rich) also hydrothermally precipitated as diagenetic phases High sanidine and specular hematite at Gale crater can result from diagenetic alteration of basaltic compositions by hydrothermal fluids